Peer-to-Peer Computing for Mobile Networks Information Discovery and Dissemination - Schulzrinne, Henning; Papadopouli, Maria; SpringerLink (Online service) (Boston, MA : Springer US, 2009)
Wireless devices are becoming smaller, more user-friendly and more pervasive. Wireless networks have been rapidly deployed for providing wireless Internet access. Peer-to-Peer Computing for Mobile Networks: Information Discovery and Dissemination explores two main research domains: mobile peer-to-peer computing and wireless networking measurements and modelling. This work presents a novel framework for mobile data discovery based on the peer-to-peer paradigm. It is designed for mobile devices that experience loss of connectivity to the Internet. It then analyzes the workload and access in large-scale wireless networks through extensive real-life measurement studies. Finally, it presents a methodology for modelling the wireless demand and access patterns. Peer-to-Peer Computing for Mobile Networks: Information Discovery and Dissemination is designed for a professional audience composed of researchers and practitioners in industry. It is also suitable as an advanced-level text or reference book for students in computer science and electrical engineering. .
7DS architecture for information sharing -- Performance analysis of information discovery and dissemination -- Empirically-based measurements on wireless demand -- Modeling the wireless user demand -- Conclusions and future work.
Keywords: Computer science; Computer organization; Computer communication systems; Multimedia information systems; E-commerce.; Electrical engineering; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Computer Systems Organization and Communication Networks; Communications Engineering, Networks; Multimedia Information Systems; e-Commerce/e-business.; Electronic books